Fibrinogen is chemotactic for vascular smooth muscle cells - Naito, Michitaka; Hayashi, Toshio; Kuzuya, Masafumi; Funaki, Chiaki; Asai, Kanichi; Kuzuya, Fumio (FEBS letters, 1989)
We studied the effect of fibrinogen on the migration of bovine aortic smooth muscle cells in culture, using a Neuro Probe 48-well micro chemotaxis chamber. Fibrinogen stimulated the migration of the cells dose-dependently at concentrations from 30 to 1OOO μg/ml. A modified checkerboard analysis of the response demonstrated that the effect was largely chemotactic in nature. The present results suggest that fibrinogen may play an important role in the pathogenesis of arterial intimal thickening and atherosclerosis.